Celebrating the 30th Anniversary of Ostrom's Governing the Commons: Traditions and Trends in the Study of the Commons, Revisited. Issue 1 (27th February 2020) - van Laerhoven, Frank; Schoon, Michael; Villamayor-Tomas, Sergio
In this editorial we assess 50 years' worth of peer-reviewed publications to establish traditions and trends in the study of the commons. Based on this assessment, we provide a sketch of how IJC and its editors can continue to contribute to the development of the field.